Antibiogram of Sputum Collected from Patients with Acute Exacerbation of Asthma (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Despite optimal guideline-directed treatment and irrespective of under lying disease severity, patients with asthma experience exacerbations due to variety of reasons including infections. Exacerbations continue to occur and impose consider able morbidity and mortality on patients and constitute a significant burden on healthcare resources. This study aimed to assess bacterial etiology in acute exacerba tion of asthma and their antibiotic resistance pattern isolated from sputum samples. Materials and methods: A cross-sectional study was conducted from September 2018 to February 2019, including 70 patients with acute exacerbation asthma from the Department of Medicine of Chittagong Medical College Hospital. Sputum samples were collected from the patients and analyzed by Gram staining, microscopy and culture. Results: Sputum culture positivity was observed in 18 cases (25.7%) and all of them were gram negative bacteria. E. coli was the most common organism isolated (44.4%), followed by Klebsiella (33.3%) and Pseudomonas (22.2%). Isolated bacteria were resistant to Ceftriaxone, Ceftazidime, Doxycycline and Tetracycline while sensitive to amikacin, ciprofloxacin, meropenem, and colistin. Patients with positive culture were older than their counterparts (51.22±7.29 vs. 40.00±13.35, p=0.001). Smoking status, presence of comorbidities and steroid use had no association with culture positivity. Conclusion: Sputum culture and sensitivity testing can be rational in patients with acute exacerbation of asthma to know its role in exacerbation as well as to know the antibiotic sensitivity as regularly used antibiotics were found resistant in most isolates.Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 52-57